Implementasi dan Analisis QoS pada Smart Door yang Terintegrasi dengan Aplikasi Telegram - Mujtahidah, Aidah Khuriatul; Oktiawati, Unan Yusmaniar (Department of Electrical Engineering and Informatics, Vocational College, Universitas Gadjah Mada, 2021)
Home security is a mandatory requirement for every homeowner. With home security, homeowners will always feel safe leaving the house for a long time. In this final project, the author made a smart door with its main components are the HC-SR04 ultrasonic sensor and web camera. The function of the ultrasonic sensor and webcam is to detect a movement in the area around the access of people. In this system, not only can it detect movement, but also send notifications in the form of text and videos through the Telegram application so that homeowners can find out if someone tries to enter the house even though the owner of the house is away from his house. The author also adds dual security in the form of a remote control system, where when the homeowner knows of theft, the homeowner simply sends a